History of pre‐eclampsia negatively impacts stroke severity postpartum in rats - Ari Kropf; Jennifer L. Anderson; Milena Esposito; Sarah M. Tremble; Marilyn J. Cipolla (Neuroprotection, 2025)
Abstract Background Pre‐eclampsia (PE) is a serious hypertensive disorder of pregnancy with lifelong deleterious effects including an increased risk of stroke postpartum (PP). In the present study, we aimed to determine whether previous PE exacerbates ischemic injury during PP and investigate the underlying mechanisms. Methods Female Sprague‐Dawley rats were studied at 4–9 months PP after either a normal pregnancy postpartum (NormP‐PP, n = 7) or experimental PE (ePE) induced using a high‐cholesterol diet (ePE‐PP, n = 9). The animals underwent transient middle cerebral artery occlusion for 2 h with 1 h of reperfusion. Dual‐site laser Doppler flowmetry was used to measure cerebral blood flow changes in the middle cerebral artery and collateral territories. Ischemic injury was measured using 2,3,5‐triphenyl tetrazolium chloride staining. Circulating 8‐isoprostane, 3‐nitrotyrosine, and oxidized low‐density lipoprotein levels were measured using enzyme‐linked immunosorbent assays. In separate groups of animals, NormP‐PP (n = 10) and ePE‐PP (n = 9) at 3–4 months PP, isolated pial collateral vessels, leptomeningeal anastomoses, and mesenteric arteries were studied using pressure myography. Results Previous ePE worsened stroke outcome in the PP period, significantly increasing infarction and edema in ePE‐PP compared to NormP‐PP animals (40.6 ± 7.6% vs. 13.7 ± 6.5%, p < 0.01; 5.1 ± 2.0% vs. 2.6 ± 0.4%, p < 0.01) despite comparable changes in cerebral blood flow in the middle cerebral artery and pial collateral territories during ischemia and reperfusion. When infarction was analyzed as a function of perfusion deficit, the ePE‐PP animals showed greater sensitivity to ischemia. Pial collaterals had increased pressure‐induced myogenic tone in ePE‐PP compared to NormP‐PP rats. Percentage tone at 80 mmHg for ePE‐PP vs. NormP‐PP was 15.5 ± 1.6% vs. 8.6 ± 1.9% (p < 0.01). ePE‐PP animals showed significantly elevated levels of circulating 8‐isoprostane and 3‐nitrotyrosine but not oxidized low‐density lipoprotein after transient middle cerebral artery occlusion (p < 0.05, and p < 0.01, respectively). Conclusions Worsened stroke outcomes after ePE pregnancy were related to increased ischemia sensitivity, increased pial collateral tone, and elevated levels of oxidative stress markers. Thus, the pathological effects of ePE persisted PP and negatively affected stroke outcomes.